أثر البرنامج التدريبي المقترح في تنمية بعض المهارات الإجتماعية واللياقة البدنية لدى الأطفال المعاقين عقليا القابلين للتدريب 11-16 سنة -المركز البداغوجي للمعاقين عقليا بالمسيلة - تركي إسحاق (University of M'Sila, 2024)
The study aimed to determine the impact of the proposed sports training program on developing some social skills for children with mental disability. The study sample included 9 students of both sexes with mental impairments (08 males and 01 female) out of a total of ten students, with one student omitted due to health reasons. Between the ages of 11 and 16, with a disability rate ranging from 55 to 70 degrees. The research sample was selected from children with mild mental disabilities - in Msila city. The experimental method was based on the pre- and post-test of one sample. The study tools consisted of applying the proposed training program consisting of 24 sessions (prepared by the researcher) for a period of 24 weeks, two sessions per week. Each session for 50 minutes. In addition to the social skills scale for the mentally disabled (prepared by Saleh Haroun 1996). Which was modified to suit the study environment. After conducting post-measurements, the study concluded that the proposed sports training program has a positive impact on the social skills and the level of physical fitness of children with mental disability.